IMPLEMENTASI KURIKULUM PAI MELALUI PROGRAM KELAS AGAMA DI MTSN 3 JOMBANG: IMPLEMENTASI KURIKULUM PAI MELALUI PROGRAM KELAS AGAMA DI MTSN 3 JOMBANG - Nisa', Khoirun; Ahmad Said; Zakariyah; Emi Lilawati (Universitas Islam Lamongan, 2024)
The Islamic religious education curriculum is always attempted to follow the flow of the wind of the development of science and technology (IPTEK), and its negative impacts that always arise to always be anticipated. One way to overcome this is by holding new innovations to keep up with the times so that the PAI curriculum or PAI learning is not set aside by students and also the improvement and repair of the PAI curriculum system in schools as a stand-alone subject or integrated with other subjects. This study focuses on (1) How is the PAI curriculum design through the religious class program at MtsN 3 Jombang (2) What are the program innovations from the development of the PAI curriculum through religious classes at MtsN 3 Jombang. This study uses a qualitative approach with a descriptive research type. Data collection was carried out using interview, observation and documentation data collection techniques. Data validity checking is done by using source triangulation technique. The research result shows that: (1) using two designs for learning in religion class, namely a) Subject Matter Design (subject design separated into 4, namely SKI, Fiqh, Al Quran Hadith, Aqidah Akhlak), b) Collaborative Design (lessons with continuity with others Al Quran Hadith with Tahfidz, Fiqh with Yellow Book, Aqidah Akhlak with Dhuha and Dzuhur congregational prayers, SKI with pilgrimage of wali 5 and PHBI). In the PAI Curriculum Innovation at MtsN 3 Jombang, namely the Religion Class Innovation which contains religious Innovation, namely Tahfidz and Yellow Book Guidance and there are programs, namely daily, weekly, and annual programs which are also implemented by the religion class.